Specialist courts for sentencing Aboriginal offenders - Bennett, Paul (The Federation Press, 2016)
Introduction -- How aboriginal courts work -- The roles of the participants -- The decision-making process -- What do aboriginal courts achieve? -- Theory and critiques -- Conclusion